2017
DOI: 10.1038/s41598-017-09695-z
|View full text |Cite|
|
Sign up to set email alerts
|

A novel ruthenium (II)-derived organometallic compound, TQ-6, potently inhibits platelet aggregation: Ex vivo and in vivo studies

Abstract: Arterial thrombosis plays a key role in cardiovascular diseases. Hence, developing more effective antithrombotic agents is necessary. We designed a ruthenium (II)-derived complex, [Ru(η6-cymene)2-(1H-benzoimidazol-2-yl)-quinoline Cl]BF4 (TQ-6), as a new antiplatelet drug. TQ-6 (0.3 µM) exhibited extremely strong inhibitory activity against platelet aggregation, Src, and Syk phosphorylation stimulated by agonists in human platelets. In collagen-activated platelets, TQ-6 also inhibited ATP-release, [Ca+2]i, P-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…TQ-6 ( Figure 1A) and its ligand (L) were synthesized according to the method used in a previous study [18]. The BV2 microglia were gifted by Professor Lin, Department of Pharmacology, School of Medicine, National Taiwan University.…”
Section: Tq-6 Synthesis and Microglia Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…TQ-6 ( Figure 1A) and its ligand (L) were synthesized according to the method used in a previous study [18]. The BV2 microglia were gifted by Professor Lin, Department of Pharmacology, School of Medicine, National Taiwan University.…”
Section: Tq-6 Synthesis and Microglia Cultivationmentioning
confidence: 99%
“…Microglia were plated into 24-well culture plates at 1 × 10 5 cells/well and cultured in DMEM. After incubating for one day, the cells were treated with either the solvent control (0.1% dimethyl sulfoxide, DMSO) or TQ-6 (1 or 2 µM) for 30 min, and then stimulated using LPS (1 µg/mL) for 24 h. Cell viability was measured using an MTT assay [18], and the viability index was calculated as follows: (absorbance of treated cells/absorbance of control cells) × 100%. The absorbance of the samples was determined at 570 nm by using an MRX absorbance reader (Dynex Technologies, Chantilly, VA, USA).…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent our studies have established that novel ruthenium based compounds TQ-5 and TQ-6 possess in vitro antiplatelet and in vivo antithrombotic effects [ 13 , 14 ]. These outcomes provided us with the impetus to further analyze the structure activity relationship of three (TQ-1, TQ-2 and TQ-3) newly synthesized ruthenium derived compounds in agonists induced washed human platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study established that a novel ruthenium-based compound TQ-5 suppressed platelet aggregation in vitro in washed human platelets via inhibiting the phosphorylation of Akt and JNK1 and subsequently reducing the ATP release reaction and intracellular calcium mobilization [ 13 ]. Another interesting study from our group also showed that the ruthenium compound TQ-6 has a novel role in inhibiting platelet activation through the inhibition of the agonist receptors-mediated inside-out signaling such as Src-Syk-PLCγ2 cascade and subsequent suppression of granule secretion, leading to disturbing integrin α IIb β 3 -mediated outside-in signaling and ultimately inhibiting platelet aggregation [ 14 ]. In this study, the structure activity relationship (SAR) of three newly synthesized ruthenium-based compounds—TQ-1, TQ-2 and TQ-3—was performed in collagen and thrombin-induced washed human platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%